The cognitive and affective roles of learning assistants in science, technology, engineering, and mathematics college classrooms: An exploration of classroom experiences and students' metacognitive awareness and disciplinary identity. Issue 3 (27th January 2022) - Kornreich‐Leshem, Hagit; Benabentos, Rocio; Hazari, Zahra; Potvin, Geoff; Kramer, Laird
Abstract: The power of knowledgeable peers (in this case undergraduate learning assistants [LAs]) to scaffold learning in ways that can positively influence both cognitive and affective outcomes in science, technology, engineering, and mathematics (STEM), is explored in this study. In terms of the cognitive perspective, we use a metacognitive awareness (MA) framework for which the MA indicator predicts course performance. For the affective perspective, we use a disciplinary identity (DI) framework for which the DI indicator predicts discipline‐specific persistence. A survey that included these indicators as well as students' experiences in STEM classes was administered to over 2000 students. Multiple regression models reveal student experiences (individually and socially) as predictors of MA and DI. Certain social learning experiences (e.g., explaining to others when the LA is present) were found to be more predictive of MA than individual learning experiences. This result provides evidence to suggest that collaborative environments may align with increased metacognitive processes. Social learning experiences (e.g., explaining to the LA) were also found to be positive and significant predictors of DI but with a smaller effect than for MA. Fully participating in group activities was found to be a significant and positive predictor of both outcomes. This study provides further evidence for the importance of active learning (both individually and socially) for both cognitive and affective outcomes as well as the growing role that LAs can play to enhance these outcomes.